ANALYSIS OF VARIABLE CALCULATION ON STARTUP ASSESSMENT : CASE STUDY PT XYZ - Bramanti, Geodita Woro; Gogor Arif Handiwibowo; Xaviera, Ameerah Rida; Agustin, Harisatul; Ninglasari, Sri Yayu; Negoro, Nugroho Priyo; Prihananto, Prahardika (Journal of Research and Technology, 2023)
Economic growth in Indonesia is increasing rapidly. In Indonesia, the growth of startups is increasing along with the continued development of the digital industry. The emergence of startups in Indonesia began in 2010 which was pioneered by the presence of startups Tokopedia and Blanja.com. PT. XYZ as a state-owned enterprise supports the development of startups by providing digital creative facilities, funding, and expanding market access, specifically to accelerate their industrial growth. The amount of funding that PT XYZ will provide to startups also varies according to the startup development stage and the company value (valuation) of the startup. The valuation calculation that is currently being carried out by PT. XYZ is by using the First Chicago method as the calculation method. However, in its application, there are still several calculation components that have not been standardized. The absence of standards for some of the components of this calculation can affect the size of the calculated startup valuation figures. This will have an indirect impact on startups, investors and stakeholders. Therefore, this study aims to analyze the standard setting on the three components of valuation calculations or business appraisals at startups carried out by PT. XYZ and to establish improvement evaluation standards for determining the three components of calculations in the first Chicago method. In this study, the results of the startup assessment are the dependent variable while the annual average growth rate, stock value size and discount rate are the independent variables. The sample population used in this study were startups who became alumni of PT. XYZ. The analytical method used is using linear regression.